2020
DOI: 10.1159/000509572
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum from Temperament to Mental Illness: Dynamical Perspectives

Abstract: Temperament in healthy individuals and mental illness have been conjectured to lie along a continuum of neurobehavioral regulation. This continuum is frequently regarded in dimensional terms, with temperament and mental illness lying at opposite poles along various dimensional descriptors. However, temperament and mental illness are quintessentially dynamical phenomena, and as such there is value in examining what insights can be arrived at through the lens of our current understanding of dynamical systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…On the other hand, the FET has shown differential effects in the presence of several categories of mental illness and in particular, differentiates between major depression, generalized anxiety disorder, comorbid depression and anxiety, and several personality and psychotic disorders ( 12 , 21 24 ). This result showing differential effects in the presence of illness makes the FET model the most promising model currently for exploring the temperament-illness continuum and the value of basing a model on neurophysiological evidence rather than lexical descriptors ( 7 , 8 , 13 , 14 , 21 24 ).…”
Section: The Temperament-mental Illness Continuummentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the FET has shown differential effects in the presence of several categories of mental illness and in particular, differentiates between major depression, generalized anxiety disorder, comorbid depression and anxiety, and several personality and psychotic disorders ( 12 , 21 24 ). This result showing differential effects in the presence of illness makes the FET model the most promising model currently for exploring the temperament-illness continuum and the value of basing a model on neurophysiological evidence rather than lexical descriptors ( 7 , 8 , 13 , 14 , 21 24 ).…”
Section: The Temperament-mental Illness Continuummentioning
confidence: 99%
“…Several authors have suggested that temperament and mental illness can be viewed as lying along some form of continuum ( 7 – 14 ). This idea can be traced back to Hippocrates who suggested that temperament and mental illness can be understood as being caused by different levels of four humors within the body.…”
Section: The Temperament-mental Illness Continuummentioning
confidence: 99%
See 3 more Smart Citations